Electromagnetic drive - Tesiana, Finnie (2018)
All current propulsion systems require propellant or external field in order to produce thrust. However, in recent years, some experiments on a propellant-less closed thruster named Electromagnetic Drive have claimed to produce thrust, up to 4 N/kWe. The mechanism of how Electromagnetic Drive produces thrust is still debatable, but its principle of operation shall not violate Newton’s 3rd law and conservation of momentum. In this report, the author first reviews the literature on Electromagnetic Drive and the existing hypotheses concerning the measured thrust. By employing the quantum tunnelling of EM wave, she shows that Electromagnetic Drive is incapable of producing thrust and therefore, any measured thrust is due to side-effects associated with the physical set-up of the thruster.